The value of the gonadotrophin-releasing hormone test as a prognostic factor in infertile patients with varicocele - Atikeler, K; Yeni, E; Semercioz, A; Yalcin, O; Baydinc, C (Wiley, 1996)
Objective To determine the value of the gonadotrophin-releasing hormone (GnRH) test in selecting which infertile patients with varicocele would benefit from varicocelectomy. Patients, subjects and methods The study comprised 30 patients with varicocele who presented between November 1993 and May 1994, and 10 control subjects. The basal serum level of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) were determined and all participants given 100 mu g of GnRH nasally. The levels of FSH and LH were then determined for up to 2 h. The patients then underwent varicolectomy and the response was evaluated by comparing sperm quality before and after treatment and between those with increased or normal FSH and LH levels in response to the GnRH test. Results Those patients who had increased FSH and LII levels after the GnRH test had a mean 121% increase in sperm density (P<0.001), a 23% increase in sperm motility (P<0.001) and a 40% decrease in sperm abnormality (P<0.05). The respective values for those with normal levels of FSH and LH were 15% (P<0.05), 11% (P>0.05) and 11% (P>0.05). Conclusion The GnRH test is useful for determining those patients who should benefit from varicocelectomy.
Keywords: varicocele; prognostic factor; GnRH test; infertility